Perancangan Rumah Tahfidz Anak dengan Konsep Arsitektur Islam - Melly Andriana; Dara Wisdianti; Gebrina Fatima Azzahra (Jurnal Teknik dan Teknologi Indonesia, 2023)
The Tahfidz Children's House is a place to deepen the memorization of the Qur'an, this Children's Tahfidz House is also intended for junior high school children, and is only intended for children who want to continue to the Islamic boarding school high school level. Tahfidz's house is located on JL. Black Crow, Sei Sekambing B, Medan – Sunggal, Medan City, North Sumatra which has many educational scopes from play groups to high schools and is very suitable for the construction area of the Tahfidz Children's House in the vicinity. The approach to this Tahfidz House is to use Islamic architecture by looking at the architecture of the heyday of Islam itself which was made as good as possible for the residents of the Tahfidz Anak House to make it easier to memorize and interpret the contents of the Qur'an quickly